Prenatal Methamphetamine Exposure and Short-Term Maternal and Infant Medical Outcomes - Shah, Rizwan; Diaz, Sabrina D.; Arria, Amelia; LaGasse, Linda L.; Derauf, Chris; Newman, Elana; Smith, Lynne M.; Huestis, Marilyn A.; Haning, William; Strauss, Arthur; Della Grotta, Sheri; Dansereau, Lynne M.; Roberts, Mary B.; Neal, Charles; Lester, Barry M. (American Journal of Perinatology, 2012)
Objective Examine maternal and infant medical outcomes of prenatal exposure to methamphetamine (MA). Study Design Four hundred and twelve mother-infant pairs (204 MA-exposed and 208 unexposed matched comparisons) were enrolled in the Infant Development, Environment and Lifestyle (IDEAL) study. Exposure was determined by maternal self-report during this pregnancy and/or positive meconium toxicology. Maternal interviews assessed prenatal drug use, pregnancy course, and sociodemographic information. Medical chart reviews provided medical history, obstetric complications, infant outcomes, and discharge placement. Results MA-using mothers were more likely to be poor, to have a psychiatric disorder/emotional illness and less prenatal care, and to be less likely to breast-feed their infant than comparison mothers. After adjusting for covariates, MA-exposed infants were more likely to exhibit poor suck, to have smaller head circumferences and length, to require neonatal intensive care unit (NICU) admission, and to be referred to child protective services (CPS). Several outcomes previously reported from studies that lacked adequate control groups or adjustment for covariates were not significantly different in this study. Conclusion Prenatal MA exposure is associated with maternal psychiatric disorder/emotional illness, poor suck, NICU admission, and CPS involvement, and MA-exposed infants were less likely to be breast-fed; however, the absence of many serious complications, such as fetal distress, chronic hypertension, preeclampsia, placenta previa, abruptio placentae, and cardiac defects, suggests confounding variables influenced prior studies.
Keywords: amphetamine; methamphetamine; drug; antenatal; neonate